Book Reviews (Blackfriars, 1930)
Book reviewed in this article: A Companion to Mr. Wells' Outline of History. By Hilaire BHelloc. The Monstrous Egimest. A Book about Queen Elizabeth. By Christopher Hollis The Mind of the Missal. By C. C. Martindale, S.J. The Risen Sun. By C. C. Martindale, S.J. Modernity. By F. L. Wheller. The Voyage Out. Jacon's Room. Mrs. Dalloway. The Common Reader. By Virginia Woolf. The Bendictineds. By Dom David Knowles. The Idea of Value. By John Laird, M.A. The Life of all Living. The Philosophy of Life. By Fulton J. Sheen, Ph.D. Pays for Puppets. A Passion Play. Spiritual Exercises of a Dominican Friar.. By F. William Perin. Little Plays of St. Benedict. S. Anselmi Opera: (1) Cur Deus Homo (2) Monologion. Recensuit d. Franciscus Salesius Schmitt, O.S.B. Mother Genevieve Dupuis. Foundress of the English Congregation of the sisters of charity of St. Paul the Apostle. 1813–1903. by the Right Rev. Monsignor Hudson. The Life and Lyrics of Richard Rolle. By Frances M. M. Comper. Le Feu de l-Amour, Le Modele de la vie Parfaite, Le Pater. Par Richard Rolle, traduits par D. M. Noetinger, moine de Solesmes. Blessed Cuthbert Mayne. By R. A. McElroy, C.R.L. Golden Memories: The Love Letters and Prison Letters of William O'Brien. Light and Leading: Light Leasders reprinted from The Times. A History of Europe. By Father Bedde Jarrett, O.P.